Hubungan Stres Kerja terhadap Kinerja Karyawan pada PT Tunas Mobilindo Parama Jakarta Selatan - Agustina, Teni; Lestari, Nurlaela Eva Puji; Rismayanti, Shella (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Human resource management is very important for companies in managing, managing and utilizing employees so that they can function productively for the achievement of company goals. Efforts to improve employee performance, including paying attention to work stress. Stress is also very influential impact on the company because it involves the performance of employees in carrying out their duties and responsibilities within the company organization. This study aims to determine the effect of work stress on employee performance in the Mechanical Engineering section of PT Tunas Mobilindo Parama. Data analysis uses Validation test, Reabilitation test, correlation coefficient test, determination test and regression equation test. This study used a saturated sample of 30 respondents from the Mechanical Engineering section at PT Tunas Mobilindo Parama. The research method in this study uses multiple linear regression method with the data processed is work stress (X) on employee performance (Y). While for the calculation of the correlation coefficient test shows that the influence of work stress has a strong or high effect on employee performance that is equal to 0.855 and for the calculation of the test of determination gets 74.2% results, which means that work stress (X) has a big effect or has a strong relationship on employee performance ( Y) with the remaining other factors equal to 25.8%. Key Words: Work Stress, Employee Performance